Energy woes [US National Energy Policy]. - Sweet, W.
The long-awaited and much-discounted National Energy Policy report, issued by a task force headed by Vice president Dick Cheney, was not the one-dimensional document critics and adversaries of the Bush administration eagerly awaited. Much of the criticism since release of the report would seem, in fact, to reflect more what people expected to read than what is actually in the report. This paper excerpts the report. In addition, for a contrasting view, the paper excerpts a report prepared by researchers at several national laboratories which presents quite a different outlook on the role fossil fuels need play in the country's energy future. In the report, the very real crisis in electricity has been bundled with concerns about increased prices for gasoline and home heating oil-increases that may prove quite transitory-to sell the public hard on an all-out effort at new production, with environmental protection given much less emphasis. What the administration seeks from the public, at bottom, is much more production of fossil fuels and streamlined or less onerous procedures for approving new plants and infrastructure
Keywords: US National Energy Policy; Electricity crisis; Energy conservation; Environmental protection; Fossil fuels; Government policy; Home heating oil; New infrastructure approval; New plants approval